PECULIARITIES OF BODY MASS COMPOSITE IN PATIENTS WITH OVERWEIGHT AND OBESITY - Kolisnyk, P.F.; Dolynna, O.V.; Kolisnyk, S.P.; Baranova, I.V.; Gumeniuk, I.P. (World of Medicine and Biology, 2018)
In the scientific literature three directions of studies of the body mass composition are distinguished: pathological changes mass of bone, muscle and adipose tissue. However, in clinical practice they are not isolated, but combined, forming a type of constitution specific for a particular person. Obesity and overweight as a manifestation of pathological changes in the fat component of body weight are common among the world’s population of all age groups and are one of the main modified risk factors for chronic non-infectious diseases. The constitutional features of the phenotype have been studied in various diseases and can be used in the selection of treatment and rehabilitation programs. The "gold standard" for the diagnosis of body mass composition is dual-energy densitometry. However, this method is used to diagnose osteoporosis and is not routinely employ in the clinic for estimating body composition. Bioelectrical impedance analysis is a non-invasive, quick, simple and cheap method for determining body composition, recommended for use European Working Group on Sarcopenia in Older People. The purpose of the research work was to study the features of the body mass composition in patients with overweight and obesity with using the method bioelectrical impedance analysis. The initial data were obtained by the method of extracting information from 98 protocols of bioelectrical impedance analysis of the body mass composite (29 men and 69 women, 18-80 years old) who were treated at the Center of Medical Rehabilitation and Sports Medicine (Vinnitsa) for the period of 2011-2017. The relationship between changes in body mass components is estimated using correlation analysis. Statistical processing of the data was carried out using the Microsoft Excel program package Microsoft Office 2010. A direct correlation was established between the mass of muscle (MMT) and bone tissue (MBT) (r=0,99, p˂0,01), skeletal muscle mass index (SMI) and MBT (r=0,85, p˂0,01). An inverse correlation was observed between the mass of adipose tissue (MAT) and muscles (r =-0,47, p˂0,01), MAT and MBT (r =-0,46, p˂0,01), SMI and МAT (r =-0,34, p˂0,01). The peculiarities of the study design (the impossibility of carrying out additional measurements) and the structure of the examined group (patients without severe pathology, the average age less than 65 years) caused the absence in the study group of patients with sarcopenia. However, was founded a direct correlation between the skeletal muscle index and the bone mass, and a negative correlation between the fat mass and skeletal muscle index. The found patterns show the relationship between pathological changes in all components of the body mass composition and the need for its integrated assessment during the development of rehabilitation programs. Thus, a comprehensive assessment of body mass composition can be used to plan and monitor the effectiveness of lifestyle modification and rehabilitation programs. The obtained results evidence of the relationship between pathological changes all components and the need for integrated assessment of body composition. Constitutional peculiarities of the phenotype can be used for a personalized approach in developing rehabilitation programs and recommendations for lifestyle modification for patient with chronic non-infectious diseases, overweight or obesity.